Find:
(i)
(ii)
(iii)
(iv)
(v)
(i) Here,
We have:

We can solve the above given fractions as follows:

=
=
Hence,
The solution for the given fraction is
(ii) Here,
We have:
– ()
We can solve the above given fractions as follows:
– ()
=
=
Hence,
The solution for the given fraction is
(iii) Here,
We have:
– ()
We can solve the above given fractions as follows:
– ()
=
=
Hence,
The solution for the given fraction is
(iv) Here,
We have:
– ()
We can solve the above given fractions as follows:
– ()
=
=
Hence,
The solution for the given fraction is
(v) Here,
We have:
 2 – 6
=  6
We can solve the above given fractions as follows:
– 6
=
=
Hence,
The solution for the given fraction is